Effects of multiple cations and sintering temperature on microstructure and dielectric properties in Na1/2Ln1/2Cu3Ti4O12 (Ln = Sm and Eu) ceramic materials - Long-Fei Yuan; Ting Zhang; Dan-Dan Han (Scientific Reports, 2023)
Abstract Na1/2Eu1/2Cu3Ti4O12 and Na1/2Sm1/2Cu3Ti4O12 dielectric ceramics were synthesized at different sintering temperatures (950, 975 and 1000 °C) by a solid-state reaction method. Phase structure, cation valence state, and dielectric properties of all sintered ceramics were systematically investigated. When the preparation temperature was changed, the Cu+ ion concentration of (Na+, Eu3+) co-doped ceramics changed faster than that of (Na+, Sm3+) co-doped ceramics. Abnormally high dielectric constants of ~ 3.17 × 104 and ~ 1.06 × 104 (at 10 Hz and 303 K) were achieved in Na1/2Sm1/2Cu3Ti4O12 and Na1/2Eu1/2Cu3Ti4O12 ceramics prepared at 950 °C, respectively. However, Na1/2Sm1/2Cu3Ti4O12 and Na1/2Eu1/2Cu3Ti4O12 prepared in high sintering temperature (1000 °C) exhibited a good frequency stability of dielectric permittivity. It was demonstrated that an increasing number of charge carriers induced by the increase of sintering temperature could lead to a competitive coexistence of two polarization mechanisms (surface barrier layer capacitor and internal barrier layer capacitor), further changing the dielectric properties of CaCu3Ti4O12-based ceramics.